LET IT SYNCH IN: DUBBING SYNCHRONIZATION STRATEGIES FOR SWEARING WORDS IN HOME ALONE MOVIES - Fernando, Kiki Nur (CrossOver, 2025)
This research aimed at finding dubbing synchronization strategies of utterances that contain swearing words in Home Alone movie. It additionally purposed to find and describe the causes of  translation shifts for swearing words from English to Indonesian. The method used in this research is  descriptive qualitative. In addition, the study used documentation as a data collection technique . The data of this research were the utterances spoken by the characters in Home Alone movie. This research used the typology of Hughes (1996) to identify and classify swearing words. It also applied  the taxonomy of Matamala (2010) in the identification and description of  dubbing synchronization strategies. It further  used the classification of translation shift by Catford (1965) in the analysis of translational changes operated in swearing words. The result of theresearch showed that there were 76 swearing expressions in total. They included 60 forms  for  stupidity, 3  for religion, 4  for anatomy, 5  for  excretion, and 4  for animal. The researcher also found 63 cases of amplification, 7  of modification, and 6 of reduction. Futhermore, the reseacher found 11  structure shifts, 25 intra-system shifts, 26  rank shifts, and 14  class shifts. Stupidity was the dominant type of swearing words uttered in the movies. Amplification was the dominant strategy used in the movies. The dominant shift was  rank or unit shift. The researcher found that the translator or dubber often changed the number of syllables in order to focus on delivering the meaning.